2019
DOI: 10.3390/nu11071654
|View full text |Cite
|
Sign up to set email alerts
|

Partially Hydrolysed Whey-Based Formulae with Reduced Protein Content Support Adequate Infant Growth and Are Well Tolerated: Results of a Randomised Controlled Trial in Healthy Term Infants

Abstract: The current study aimed to investigate growth, safety and tolerance of partially hydrolysed infant formulae in healthy full-term infants. Fully formula-fed infants were randomised ≤14 days of age to receive a partially hydrolysed whey formula with 2.27 g protein/100 kcal (pHF2.27) or the same formula with 1.8 g or 2.0 g protein/100 kcal (pHF1.8 and pHF2.0) until 4 months of age. The primary outcome was equivalence in daily weight gain within margins of ± 3 g/day; comparison with WHO Child Growth Standards; gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 28 publications
4
10
0
1
Order By: Relevance
“…The voluntary blood sample obtained in a subgroup of infants at 17 weeks of age did not reveal any statistically significant differences between intervention groups. The serum urea levels are within normal ranges and the values for the subgroup of the PHF-fed infants observed in the current study (median of 18.0 mg/dL) are in line with previously reported values for 4-month-old infants consuming this PHF (median of 20.5 mg/dL) [ 19 ]. Interestingly, breastfed infants had lower serum urea levels and a lower body weight at four months of age compared to both formula groups, as reported previously [ 34 , 35 ], and this can be (partially) attributed to differences in protein quality and quantity [ 36 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The voluntary blood sample obtained in a subgroup of infants at 17 weeks of age did not reveal any statistically significant differences between intervention groups. The serum urea levels are within normal ranges and the values for the subgroup of the PHF-fed infants observed in the current study (median of 18.0 mg/dL) are in line with previously reported values for 4-month-old infants consuming this PHF (median of 20.5 mg/dL) [ 19 ]. Interestingly, breastfed infants had lower serum urea levels and a lower body weight at four months of age compared to both formula groups, as reported previously [ 34 , 35 ], and this can be (partially) attributed to differences in protein quality and quantity [ 36 ].…”
Section: Discussionsupporting
confidence: 92%
“…In our study, a significantly lower body weight was observed at 8 and 13 weeks of age in the PHF (and the breastfed reference group) versus the IPF group, which was not paralleled by any statistically significant differences in length or head circumference outcomes. Confirming previous findings [ 19 ], we observed infant growth outcomes for the PHF group that were close to those of breastfed infants and to the WHO growth standard median, indicative of normal infant growth. In addition, as evident from the demonstrated equivalence in daily weight gain, length gain and head circumference gain in the randomized groups, the current study confirms the suitability and nutritional adequacy of this PHF in comparison to a standard IPF, following stringent evaluation according to regulatory guidelines [ 20 , 21 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Non-inferior weight gain was also shown in another trial of infants fed a pHF-W (1.9 g/100 kcal) vs. extensively hydrolyzed protein formula (2.3 g/100 kcal) ( 37 ). To our knowledge, only one previous study has assessed pHF-W formula with a protein level below this range; Rigo et al ( 38 ) showed that infants fed with pHF-W containing 1.8 g protein/100 kcal had equivalent weight gain from enrollment (≤14 days of age) to 4 months compared to infants fed pHF-W with 2.27 g protein/100 kcal.…”
Section: Introductionmentioning
confidence: 99%
“…To obtain hydrolysates, various raw materials of animal (dairy, meat, fish) and vegetable (soy, lentils, beans, chickpeas) origin with a high protein content are used. Thus, the protein component of modern hypoallergenic formulae for infants is represented by extensively or partially hydrolysated milk proteins [9], such as whey, casein proteins or mixtures thereof [10]. Although whey proteins have a balanced composition of essential amino acids [11], β-lactoglobulin, which accounts for 58% of whey proteins (12% of total protein), has the highest allergenic potential [12,13].…”
Section: Introductionmentioning
confidence: 99%